2012
DOI: 10.1016/j.biopsych.2011.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic Modulation of Auditory Information Processing in the Human Brain

Abstract: Background Auditory mismatch negativity (MMN) and P300 event related potentials (ERP) are reduced in schizophrenia patients, and healthy volunteers administered the N-methyl-D-aspartate (NMDA) glutamate receptor antagonist, ketamine. In rodents, N-acetylcysteine (NAC), a stimulator of the cystine-glutamate exchanger, attenuates the cognitive and behavioral effects of NMDA receptor antagonists. Based on these findings, we tested whether NAC would reduce ketamine effects on behavior, MMN, and P300 in healthy hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 72 publications
9
62
0
Order By: Relevance
“…This finding is consistent with previous studies in the auditory and visual domains (47)(48)(49)(50)(51)(52)(53)86) although we observed a strong effect only in the encoding phase with the retrieval significance reduced to a trend. We also found a trend for correlation between P300 and cognitive performance under ketamine for both encoding and retrieval conditions.…”
Section: P300supporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with previous studies in the auditory and visual domains (47)(48)(49)(50)(51)(52)(53)86) although we observed a strong effect only in the encoding phase with the retrieval significance reduced to a trend. We also found a trend for correlation between P300 and cognitive performance under ketamine for both encoding and retrieval conditions.…”
Section: P300supporting
confidence: 93%
“…However, there is surprisingly little known about the influence of ketamine on the neurophysiological changes measured with ERPs in the context of WM processes. Studies so far have focused on auditory oddball paradigms and reported reductions in P300 as well as a marker of automatic WM update, mismatch negativity (47)(48)(49)(50). Visual experiments have focused exclusively on later ERP components, reporting an attenuation of the P300 component (51)(52)(53).…”
Section: Q4mentioning
confidence: 99%
“…Given that sub-anesthetic doses of NMDAR antagonists, including ketamine, transiently induce schizophrenia-like positive, negative, and cognitive symptoms (53-55, 57, 62, 70-72), NMDAR antagonists provide a pharmacological tool for probing the potential role of NMDAR hypofunction in generating these symptoms in both animal (73-77) and human (53-56, 59-62, 78-82) studies. Such studies implicate NMDAR function in predictive coding-based learning and remembering the recent stimulus history (2, 34, 39, 52).…”
Section: Introductionmentioning
confidence: 99%
“…At the neurochemical and anatomical levels MMN has been shown to reflect impaired Nmethyl-D-aspartate receptor (NMDAR) function [12][13][14][15] at the level of supratemporal auditory cortex in schizophrenia 2,[15][16][17][18] . By contrast, ensemble-level processes contributing to MMN impairments have been studied to a lesser degree.…”
Section: Introductionmentioning
confidence: 99%
“…In ERSP analysis, electrophysiological activity is divided conventionally into discrete delta (.5-4 Hz), theta (4-7 Hz), alpha (7)(8)(9)(10)(11)(12), beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and gamma (>24 Hz) bands, which reflect differential underlying local-circuit processes 20,[27][28][29] . Within these bands, stimulus-related activity is further differentiated into those that reflect alterations in phase reset mechanisms as reflected in intertrial coherence (ITC) vs. those that reflect alterations in single-trial power (e.g.…”
Section: Introductionmentioning
confidence: 99%